2004
DOI: 10.1001/archsurg.139.11.1148
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a New Fibrin Sealant With Standard Topical Hemostatic Agents

Abstract: Background: Bleeding following liver resection continues to be a significant morbidity of the procedure. Fibrin sealants represent an improvement over conventional topical hemostatic agents, because they contain components that actively form clot. However, most available agents contain nonhuman protein, which represents an immunologic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
11

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 17 publications
3
99
0
11
Order By: Relevance
“…38,39 Current scientific evidence suggests beneficial effects in reducing the time to hemostasis and in lowering the requirements for perioperative RBC transfusions. [39][40][41][42][43] Although the beneficial effects of fibrin sealants have also been confirmed in a recent Cochrane review, 44 the efficacy of fibrin sealant in liver surgery has recently been questioned. 45 In a large, randomized, controlled trial in 300 patients undergoing partial liver resection, Figueras and associates 45 found no difference in total blood loss, transfusion requirements, or postoperative morbidity between patients treated with fibrin sealants (n 5 150) and a control group without fibrin sealants (n 5 150).…”
Section: Topical Hemostatic Agentsmentioning
confidence: 99%
“…38,39 Current scientific evidence suggests beneficial effects in reducing the time to hemostasis and in lowering the requirements for perioperative RBC transfusions. [39][40][41][42][43] Although the beneficial effects of fibrin sealants have also been confirmed in a recent Cochrane review, 44 the efficacy of fibrin sealant in liver surgery has recently been questioned. 45 In a large, randomized, controlled trial in 300 patients undergoing partial liver resection, Figueras and associates 45 found no difference in total blood loss, transfusion requirements, or postoperative morbidity between patients treated with fibrin sealants (n 5 150) and a control group without fibrin sealants (n 5 150).…”
Section: Topical Hemostatic Agentsmentioning
confidence: 99%
“…15 Perhaps the largest impediment to this therapy in the acute laparoscopic setting, other than getting the material to the site of injury, is the prolonged preparation time of up to 40 minutes to reconstitute these products. 24 Matrix hemostats, such as FloSeal (Baxter Healthcare, Deerfield, IL), use a special bovine collagen gelatin matrix that is cross-linked by glutaraldehyde. 25 Like fibrin sealants, they require preparation with thrombin before application.…”
Section: Humphreys Et Al 1378mentioning
confidence: 99%
“…Karaciğer ve dalak cerrahisinde kullanımının kanama kontrolündeki etkisi gösteril-miştir. [9][10][11][12][13] Ankaferd Blood Stopper ® (ABS) son yıllarda klinik kullanıma giren, bitkisel kökenli, topikal hemostatik ajandır. Hemostazı, kanama pıhtılaşma faktörle-rinden bağımsız olarak, enkapsüle protein ağı ile fokal eritrosit agregasyonunu sağlayarak gerçekleştirir.…”
Section: Resultsunclassified
“…Ameliyat süresinin kısalması için, kanamanın kontrolünde topikal hemostatiklerin kullanımı da cerraha avantaj sağlayabilir Günümüz-de Japonya'da topikal hemostatiklerin karaciğer cerrahisinde standart bir endikasyon olmadan kullanımı %60'a kadar çıkmıştır. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Bu ajanların seçiminde cerrahın tercihi kadar, hemostatik materyalin yapısı, kanamanın ciddiyeti, acil ya da elektif cerrahi yaklaşımlar gibi faktörler oynar. Fiyat, uygulama kolaylığı ve muhafaza edilme özellikleri de seçimi etkilemektedir.…”
Section: Discussionunclassified